2011
DOI: 10.1021/ja206414m
|View full text |Cite
|
Sign up to set email alerts
|

Site, Rate, and Mechanism of Photoprotective Quenching in Cyanobacteria

Abstract: In cyanobacteria, activation of the Orange Carotenoid Protein (OCP) by intense blue-green light triggers photoprotective thermal dissipation of excess absorbed energy leading to a decrease (quenching) of fluorescence of the light harvesting phycobilisomes and, concomitantly, of the energy arriving to the reaction centers. Using spectrally resolved picosecond fluorescence, we have studied cells of wild-type Synechocystis sp. PCC 6803 and of mutants without and with extra OCP (ΔOCP and OverOCP) both in the unque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
165
3
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 135 publications
(191 citation statements)
references
References 61 publications
(126 reference statements)
20
165
3
1
Order By: Relevance
“…Our results clearly demonstrate that OCP protects the photosystems and cells via two different mechanisms: by quenching of excess excitation energy (Wilson et al, 2006;Rakhimberdieva et al, 2010;Tian et al, 2011), and thereby decreasing charge separations at the reaction centers, and by quenching 1 O 2 , which is formed during the light reactions that still occur in the reaction centers and in the antennae. These two protecting mechanisms complement each other.…”
Section: Ocpmentioning
confidence: 72%
“…Our results clearly demonstrate that OCP protects the photosystems and cells via two different mechanisms: by quenching of excess excitation energy (Wilson et al, 2006;Rakhimberdieva et al, 2010;Tian et al, 2011), and thereby decreasing charge separations at the reaction centers, and by quenching 1 O 2 , which is formed during the light reactions that still occur in the reaction centers and in the antennae. These two protecting mechanisms complement each other.…”
Section: Ocpmentioning
confidence: 72%
“…OCP-mediated NPQ is more active in HL conditions (El Bissati et al, 2000), whereas we have shown that the Flv2/Flv4-mediated electron transfer mechanism is active in LC conditions already at GL. Moreover, upon exposition of cells to 350 mmol photons m 22 s 21 of blue light for 1 h, only about 29% of the PBs were quenched by the OCP mechanism in vivo (Tian et al, 2011). This observation implies that the Flv2/Flv4 heterodimer might be important at the acceptor side of those PSII complexes that received a correct energy transfer from PBs.…”
Section: Pbs Are Necessary For Flv2/flv4-mediated Photoprotection Mecmentioning
confidence: 99%
“…The C-terminal domain cannot function as a photosensor without a light absorbing chromophore. The N-terminal effector domain, when bound to the PB, requires 39-hECN to directly dissipate energy in the OCP induced photoprotective mechanism (Tian et al, 2011(Tian et al, , 2012Stadnichuk et al, 2012). The OCP thus represents a remarkably minimized system in which sensor and effector domains share a single chromophore that is critical to both photosensory and photoprotective function.…”
Section: A Revised Model For Ocp Functionmentioning
confidence: 99%